2004
DOI: 10.1038/sj.jhh.1001695
|View full text |Cite
|
Sign up to set email alerts
|

Effective control of hypertension: a project of the Hungarian society of hypertension, baseline data

Abstract: The aim of the project is to assess the quality and improve the preventive and curative practices at the primary care level in Hungary. A total of 50 general practitionaires were selected on a voluntary basis in Budapest, Hungary, and from them, 30 were randomized to the intervention (I) group and 20 to the reference (R) group. The members in the I group have been trained for the official hypertension guideline and their everyday work is monitored. Those in the R group have only been monitored to measure the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Physicians advised all recommended non-pharmacological measures to less than a half of all the hypertensive patients. The results are similar in Germany [29] and better than results from Hungary, which showed that only one quarter of hypertensive patients got all recommended non-pharmacological measures in hypertension [30].…”
Section: Comparison Of Our Own Results With the International Literat...supporting
confidence: 54%
See 2 more Smart Citations
“…Physicians advised all recommended non-pharmacological measures to less than a half of all the hypertensive patients. The results are similar in Germany [29] and better than results from Hungary, which showed that only one quarter of hypertensive patients got all recommended non-pharmacological measures in hypertension [30].…”
Section: Comparison Of Our Own Results With the International Literat...supporting
confidence: 54%
“…Almost two thirds of the patients had combined antihypertensive therapy, most frequently a fixed combination of two different drugs. The proportion of patients on combined therapy is similar to other European countries [29,30,33]. In case of three or more different classes of antihypertensive drugs, a diuretic was included in such a combination.…”
Section: Comparison Of Our Own Results With the International Literat...mentioning
confidence: 88%
See 1 more Smart Citation
“…In more than 25% of treated HT patients, the target blood pressure (BP) is not reached [1][2][3] . Around 90-95% of the cases involve primary HT (PHT).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] A Swedish study estimates that, among an adult population of 1.8 million, 60% have mild HT (140-159/90-99 mmHg), 30% moderate HT (160-179/100-109 mmHg) and 10% very high HT (X180/ X110). 1 In a representative German nationwide primary care sample, the point prevalence of HT was reported as 40.1%.…”
Section: Introductionmentioning
confidence: 99%